Resistance Pattern of Pseudomonas aeruginosa in a Tertiary Care Hospital of Kanchipuram, Tamilnadu, India - S., Senthamarai (JCDR Research and Publications (P) Limited, 2014)
Purpose: This study was undertaken to analyze the extended spectrum of β lactamase (ESBL), metallo β lactamase (MBL) & AmpC production in Pseudomonas aeruginosa in various clinical samples. Materials & Methods: One hundred four non repetitive clinical specimens were inoculated onto nutrient agar, blood agar and incubated at 37(o)C overnight. The colonies were tested for oxidase test and other biochemical tests and antibiogram. ESBL screening was done using 3(rd) generation cephalosporins and confirmatory combined double disc test, imipenem-EDTA double disc synergy test for MBL enzyme and AmpC test using Cefoxitin disc. Results & Analysis: Out of 104 P.aeruginosa isolates, 42.30% were ESBL producer, 15.38 % MBL producer and none were AmpC producer. Imipenem, Ofloxacin, and aminoglycosides (amikacin (29.8%) tobramycin (29.8%) and netilmycin (13.46%) has got the better antipseudomonal activity in this study. 43 (41.35%) P.aeruginosa was found to be Multi Drug Resistant (MDR). Conclusion: This study highlights the prevalence of ESBL, MBL and MDR P.aeruginosa. Carbapenems and aminoglycosides are promising drugs with antipseudomonal activity in our study.